2013
DOI: 10.1074/jbc.m113.470765
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from Retinal Astrocytes Contain Antiangiogenic Components That Inhibit Laser-induced Choroidal Neovascularization

Abstract: Background: It is unknown whether the exosomes derived from neurosensory retinal cells regulate angiogenesis in the eye. Results: Exosomes from retinal astrocytes contain multiple antiangiogenic components that inhibit laser-induced choroidal neovascularization. Conclusion: Exosomes from monolayer culture of retinal astrocytes, but not retinal pigment epithelium, are antiangiogenic. Significance: Retinal astrocyte exosomes might be a potential for clinical applications in the treatment of choroidal neovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 43 publications
4
115
0
Order By: Relevance
“…Exosomes derived from astrocytes exhibit endostatin-dependent antiangiogenic properties that inhibit laser-induced choroidal neovascularization. 64 Increased oxidative stress and negative regulation of vascular endothelial growth factor pathways contribute to the antiangiogenic effect of lymphocytic microparticles. 65 Interestingly, identification of newly discovered microRNA cargos in circulating microvesicles and exosomes provides promising biomarkers of angiogenic potential in patients with critical limb ischemia or diabetes mellitus.…”
Section: Extracellular Microvesicles As Intercellular Messengersmentioning
confidence: 99%
“…Exosomes derived from astrocytes exhibit endostatin-dependent antiangiogenic properties that inhibit laser-induced choroidal neovascularization. 64 Increased oxidative stress and negative regulation of vascular endothelial growth factor pathways contribute to the antiangiogenic effect of lymphocytic microparticles. 65 Interestingly, identification of newly discovered microRNA cargos in circulating microvesicles and exosomes provides promising biomarkers of angiogenic potential in patients with critical limb ischemia or diabetes mellitus.…”
Section: Extracellular Microvesicles As Intercellular Messengersmentioning
confidence: 99%
“…Nevertheless, it has been established that retinal astrocytes are able to counteract pro-angiogenic stimuli through releasing of exosomes loaded with angio-suppressors, i.e. endostatin and pigment-endothelium derived factor (PEDF) [19]. Meanwhile, astrocytes appeared to be capable of producing and secreting proteolytically active matrix metalloproteinases (MMP) and Pm, representing proteinases responsible for Pg cleavage and angiostatin formation [20].…”
Section: The Purpose Of the Present Study Was To Examine The Plasminomentioning
confidence: 99%
“…In respect of this, astrocytes are of particular interest due to the three reasons: 1) astrocytes are the most frequent cells in the CNS, which emulate the metabolic activity of neurons; 2) astrocytes play a pivo tal role as "communicators" between neurons and endotheliocytes; 3) astrocytes have been shown to produce and release several negative regulators of angiogenesis, i.e. endostatins, and have all the necessary proteinase and enzyme cascades to decompose Pg to yield angiostatins [17,19,20]. So far, there are no data available on this function of brain astrocytes.…”
Section: Fig 2 Representative Fluorescence Micrographs Of Plasminogmentioning
confidence: 99%
“…1E). These data indicate that intact exosomes were successfully isolated.Integrin β1 protein levels are downregulated by macrophage-derived exosomes in primary endothelial cells Recent reports have suggested that exosomes are potent regulators of cell migration through intercellular communication [26,27]. We determined the effect of macrophage-derived exosomes on endothelial cells by isolating macrophage exosomes from the conditioned medium of differentiated THP1 cells.…”
mentioning
confidence: 99%